Development of Students’ Professional Mobility in Foreign Languages by Pedagogical Conditions (Eurasian Journal of History, Geography and Economics, 2023)
Pedagogical conditions are conditions that ensure the effectiveness of the pedagogical system and the success of the pedagogical process. Pedagogical conditions mean a set of possibilities, methods, organizational forms and material possibilities of its implementation.